SPIRITUAL MENTAL GUIDANCE WITH ISLAMIC PSYCHOTHERAPY FOR CLIENTS OF SOCIAL REHABILITATION CENTER - Nur Azizah; Alief Budiyono; Nela Amalia; Adhitya Ridwan Budhi Prasetyo Nugroho (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Drug abuse can cause dependence and many effects, among which the impact can occur on the mental and spiritual. Mental and spiritual damage can influence drug abuse. Rehabilitation is one solution to cure drug abuse. This research aims to find Islamic Psychotherapy-Based Spiritual Mental Guidance for Clients of the Social Rehabilitation Center for Drug Abuse Victims Satria in Baturraden. This research is carried out by providing insight and knowledge to students of the Islamic Guidance and Counseling study program regarding the implementation of Islamic Psychotherapy-Based Spiritual Mental Guidance for Clients of the Social Rehabilitation Center for Drug Abuse Victims Satria"in Baturraden. The results of research where Islamic Psychotherapy-Based Spiritual Mental Guidance for Clients is carried out through religious activities or activities, including congregational prayers, reciting the Qur'an, islamic study, Hadrohan, khitobah, fasting, and other activities. The implementation of Spiritual Mental Guidance is carried out by paying attention to the needs of residents and providing religious understanding to strengthen self-awareness to change for the better.